(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To survey the use of surgical antibiotic prophylaxis at Nguyen Dinh Chieu Hospital - Ben Tre from January 1, 2019 to September 30, 2019. Method: A descriptive cross-sectional study was conducted on all medical records of surgical patients who received antibiotic prophylaxis at Nguyen Dinh Chieu Hospital - Ben Tre during the study period. Data collected included types of antibiotics, combination regimens, route of administration, and timing of the first dose. Results: A total of 2722 instances of antibiotic use were recorded. Amoxicillin/Sulbactam accounted for the highest proportion (28.6%), followed by Metronidazole (27.6%) and Ceftezol (19.1%). Single-antibiotic regimens represented 50.5% of all cases, predominantly Penicillin combined with β-lactamase inhibitors (63.3%). Regarding the route of administration, intravenous injection was predominant, accounting for 60.7% of cases. However, the timing of antibiotic prophylaxis was not optimal: only 3.2% of patients received the first dose within 120 minutes before incision, while 66.1% received it within one hour after surgery. Conclusion: The use of surgical antibiotic prophylaxis at Nguyen Dinh Chieu Hospital - Ben Tre showed several limitations, particularly regarding the choice of antibiotics and timing of administration. It is necessary to establish internal hospital guidelines for antibiotic prophylaxis to improve infection prevention effectiveness and reduce the risk of antimicrobial resistance